Industry-university partnership through experiential project-based learning: A Singapore case study - PAN, Gary (Institutional Knowledge at Singapore Management University, 2017)
A radical approach to preparing university students with future work skills, by combining academic with experiential learning through real projects faced by client partners. Learn how a university can create opportunities for collaborative learning and a tripartite learning relationship for academia, students and industry. Outcomes and impact of the case Post-module feedback surveys conducted over AY2015/16 showed that over 80% of the students who took an SMU-X module reported enhanced problem-solving, analytical, reasoning and communication skills, all of which were skills highly valued by employers. These results also dovetailed with SMU-X’s learning outcomes. More than 85% felt that the SMU-X module met their expectations and would recommend it to their peers and juniors. Students also appreciated the chance to extend their learning beyond hypothetical classroom exercises, while companies learnt and benefitted from fresh perspectives provided by students and faculty. Below are some examples of qualitative feedback received from students and client partners: "This course has allowed me to apply what I know to a real-life problem, while the opportunity to work in cross-function teams closely mirrors how we are expected to work in the real world. The process of brainstorming for solutions to the project really was an eye-opener, as it exposed me to viewpoints and opinions I would not have thought about, particularly since my other group members have had really different experiences and education from myself." - Student from Managing Information Systems for Business Value "SMU-X courses provide an essential link for students to apply what they learn in the classroom to real world business issues. On the other end, businesses benefit from a set of fresh eyes from a third party observer who can identify opportunities and inefficiencies and communicate them in a manner free from corporate hierarchy." – Mr John Ang, CEO, VRM Biologik (client partner for The Design of Business)Besides these encouraging response, SMU-X’s pedagogical approach to enhance presence learning and prepare students with future work skills received support from Singapore’s Ministry of Education in the form of a Tertiary Education Research Fund (TRF) grant in November 2015. The TRF grant supports applied educational research on a competitive basis across institutions of higher learning in Singapore. SMU-X’s innovative pedagogy has also been lauded by global accreditation body Association to Advance Collegiate Schools of Business International as one of the "Innovations That Inspire". SMU is the only institution in Singapore, and one of the three in Asia to be recognised. At the Straits Times Education Forum held on 25 June 2016, Mr Ong Ye Kung, Singapore’s Acting Minister for Education (Higher Education and Skills), cited SMU-X as an example of real-life learning which provided the environment for students to gain both depth and breadth in their skill sets via involvement in industry projects. SMU endeavours to be Asia's leading university in experiential project-based learning. Besides sharing its model with institutions in the region, SMU would like to foster global partnerships and joint programmes with peer universities. In pursuit of excellence, SMU will continue to seek external funding to conduct research on the SMU-X learning model so as to hone it further. One of the least explored yet most challenging areas in higher education is assessment of project-based learning. This is largely due to the open-ended, authentic and complex nature of the projects that students undertake. Each project is unique in terms of technical- and people-related challenges, as well as the amount of personalised learning. Therein lie valuable research opportunities which will further strengthen the efficacy of SMU-X pedagogy.Operational-wise, client recruitment and management processes will be introduced to strengthen client engagement. Efforts will also be dedicated to help students learn how to communicate and work better with client partners through “preflection” activities such as having introductory presentations to walk them through the challenges prior the start of each module. Successful students from past modules will also be invited to share their learning experience.